Mineral Content and Antioxidant Capacity of Cookies Formulated with Spinach and Pangas Catfish - Harlyanti Muthma'innah Mashar; Lamia Diang Mahalia; Sukmawati Ahmad Damiti (Jurnal Kesehatan Masyarakat, 2025)
Spinach is a leafy green vegetable that contains various nutrients and antioxidant compounds. Meanwhile, Pangas catfish contains calcium and minerals that are very good for health. Spinach and Pangas catfish can be utilized as raw ingredients to manufacture functional food products in the shape of cookies, increasing the nutritional value and antioxidant content of the cookies to increase the fulfillment of food and public health needs. This research was conducted from February to July 2024. Cookies were prepared with three variations of spinach flour to Pangas catfish flour ratio designated as F1 (45:15), F2 (30:30), and F3 (15:45). Analysis of mineral, vitamin C, TPC, TFC, and antioxidant activity was performed on each cookie formula. The study results showed that the mineral content in terms of potassium and calcium was in the range of 323.538 to 671.186 mg/100g and 44.307 to 93.006 mg/100g, respectively. Meanwhile, the bioactive compounds in the form of vitamin C, TPC, and TFC were in the range of 9.92 to 20.02 mg/100g, 16.74 to 24.97 mg GAE/g, and 32.55 to 110.84 mg QE/g, respectively, and the antioxidant activity was 8.11-17.84%. The cookies prepared using the formula F1 showed significant content of minerals, i.e., potassium and calcium, vitamin C, TPC, TFC, and significant antioxidant activity. These cookies have the potential to be developed as a functional food product that is rich in nutrients and antioxidants to better meet the nutritional and public health needs.